Noninvasive Monitoring and Neurointerventional Management of Idiopathic Intracranial Hypertension - Lang, Matthew; Mathew, Sunu; Harris, Alon; Tejada, Juan; Kovoor, Jerry M. (Journal of Clinical Interventional Radiology ISVIR, 2020)
Idiopathic intracranial hypertension (IIH) is characterized by isolated rise in intracranial pressure (ICP) leading to chronic, debilitating headaches, tinnitus, and vision loss. Conventional diagnostics and monitoring primarily require the use of invasive procedure like lumbar puncture to measure ICP, while traditional management strategies involve weight reduction and medical treatment with acetazolamide. In an effort to reduce the need for invasive procedures, noninvasive methods of ICP monitoring such as optic nerve sheath diameter measurements and two-depth transcranial Doppler ultrasonography have been developed. In cases of refractory and fulminant IIH, surgical management strategies such as optic nerve sheath fenestration (ONSF), ventriculoperitoneal (VP) and lumboperitoneal (LP) shunting, and transverse venous sinus stenting are used to relieve symptoms via ICP reduction. While ONSF and VP/LP shunting exhibit utility primarily for the treatment of vision loss and headache, respectively, venous sinus stenting may prove to be an effective option in the management of all symptoms of IIH. Most importantly, consideration of the patient’s individual symptoms and values should be taken into account when choosing the optimal surgical management strategy for patients with IIH.
Keywords: idiopathic intracranial hypertension; optic nerve sheath; transcranial Doppler ultrasonography; optical coherence tomography; electroretinography; ventriculoperitoneal shunt; lumboperitoneal shunt; venous sinus stenting